Recent advances in flavonoids from the genus Polygonatum: extraction and processing methods - Tang, Zhen-Xing; Ye, Xin-Pei; Jiang, Zhong-Bao; Chen, Yan-Xi; Shen, Hui-Yang; Hu, Yan-Yu; Shi, Lu-E (Frontiers in Sustainable Food Systems, 2025)
The genus Polygonatum is recognized for both its medicinal and food applications. It demonstrates a range of beneficial activities, making it a strong candidate for the development of health-promoted products. The activities, including hypoglycaemic, antioxidant, anti-fatigue, immune regulatory, anticancer, antibacterial and anti-atherosclerotic properties, are highly associated with various substances, including polysaccharides, saponins, alkaloids, flavonoids, and many others. Flavonoids in the genus Polygonatum are regarded as being one of the primary functional constituents, exhibiting a broad spectrum of molecular structures and bioactivities. Among them, flavonoids such as homoisoflavonoids, chalcones, isoflavones, and flavones, have been identified in the genus Polygonatum. Many studies have indicated its capacity to manifest various kinds of potently biological functions, for instance, anti-tumor, anti-viral, and glycemic control properties. Various processing methods, notably nine steam-nine bask, have been investigated. It has been observed that various chemical constituents including flavonoids, and pharmacological activities undergo significant alterations following processing. This present study aims to offer a review of the current research state on the extraction and processing of Polygonatum flavonoids, providing a theoretical foundation for their scientific advancement and reasonable utilization of Polygonati Rhizoma in food industry.